49words: An active alert hypnosis protocol for stress regulation. Issue 4 (3rd April 2023) - Wark, David M.
ABSTRACT: People, worldwide, are in dire need of stress regulation. This paper presents a six step alert self-hypnosis protocol that individuals can use to regulate a wide variety of stresses. A brief anonymized case reports from a diverse range of clients follows the protocol's six step outline. The step-by-step algorithm can be modified to address the unique circumstances of each client. Finally, summaries of neuroscience research provide possible explanations for the observed efficacy of the approach.